Effect of Municipal Solid Waste Compost on Tomato and Maize Plants - Madasamy Arun Kumar; Ammaiyappan Selvam (The Bioscan, 2025)
This study aimedto evaluate the effects of the municipal solid waste (MSW) compost application rate on soil physicochemical properties and growth of two crops plants, Tomato (Solanum lycopersicum L.) and Maize (Zea mays L.).Municipal solid waste composted with dry leaves (DL) and dry leaves + premature compost (DL+PMC) as bulking agents were applied to the soil at 10% and 20% with the following treatments: 10% MSW+DL (T1),20% MSW+DL (T2), 10% MSW+DL+PMC+10% (T3), and 20% MSW+DL+PMC+20% (T4) while soil without compost served as control. Experiments was conducted in 3-L pots and placed in greenhouse in randomized block design. Plant height, number of leaves per plant, root length, and biomass of the plants were monitored up to 60 days to evaluate the growth and quality of the plants. The results revealed that the application of both the composts (MSW+DL+PMC and MSW+DL) of municipal solid waste (MSW) compost at 20%, equalling to a rate of 400 t ha−1, significantly improved soil fertility and growth of plants.